Relationship between floating toe score and performance in track and field athletes - Yohei Yamazaki; Hiroaki Noro; Keiichiro Hata; Misato Ishikawa; Hiyo Inaba; Kazuhiko Yamazaki; Ryoichi Murayama; Hideyuki Arikawa; Aya Miyamoto; Toshio Yanagiya (PLoS ONE, 2025)
This study explored the relationship between floating toes and athletic performance among collegiate track and field athletes. A total of 422 athletes (sprinters, jumpers, and distance runners) and 136 controls participated in this study. Plantar surface images were captured using a specially designed foot scanner during standing to calculate the floating toe score. The score, which sums the floating toe points of all toes, categorizes them into ‘floating toe’, ‘incomplete contact’, or ‘normal toe’. The World Athletics score served as a measure of athletic performance. Overall, collegiate track and field athletes had a significantly higher mean floating toe score (14.22 ± 4.87 points) than controls (11.06 ± 6.05 points) (p < 0.05), suggesting that fewer floating toes may confer a performance advantage. Within the track and field events, sprinters and jumpers showed significantly higher floating toe scores than distance runners (p < 0.05), emphasizing the variations in floating toes across different events. Although no significant correlation between floating toe score and World Athletics score was observed overall, a significantly negative correlation was found among distance runners (r = -0.25, p = 0.006), indicating that distance runners with higher athletic performance tend to have more pronounced floating toes. These findings suggest a nuanced relationship between floating toes and various aspects of track and field performance, particularly in distance running.